A catalyst for polyolefin hydrocracking reaction is a ZSM-5 zeolite molecular sieve in which Ru is supported and Ce is doped in situ

CN122895033APending Publication Date: 2026-10-13NANJING TECH UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202610729070.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-05-26
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

[0005]公开号为CN121449485A:采用Ru负载介孔CeO2催化剂,应用于聚烯烃塑料加氢裂化制甲烷,缺点是贵金属钌成本高、载体机械强度不足,且产物单一、反应仍需中压氢气条件

Benefits of technology

[0024]本发明的催化剂,Ru纳米颗粒平均粒径小(约2.3 nm)、分散均匀,与Ce物种及沸石骨架产生强金属-载体相互作用,结构稳定性好。将该负载Ru纳米颗粒原位掺杂Ce原子的ZSM-5沸石分子筛在聚烯烃加氢裂解反应中作为催化剂应用时,具有催化转化率高(接近100%)、甲烷选择性优异(可达99%)的优点,TON达6317,TOF达3158 h-1,甲烷时空收率达495gCH4·gcat-1h-1;同时,通过温和调控反应条件,可实现产物从甲烷向乙烷的定向切换,乙烷产率最高可达37%,展现出灵活的产物可调性。此外,该催化剂循环稳定性好、贵金属利用率高,在废弃聚烯烃塑料的化学升级回收领域具有良好的工业应用前景。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122895033A_ABST
    Figure CN122895033A_ABST
Patent Text Reader

Abstract

The application discloses a catalyst for polyolefin hydrocracking reaction and relates to the technical field of catalyst preparation. Cerium nitrate hexahydrate is added into a mixed solution of water and hydrochloric acid, and then tetraethyl orthosilicate is slowly added as a silicon source to form a hydrolysis solution by stirring at room temperature; sodium metaaluminate is dissolved in a tetrapropylammonium hydroxide template agent, the above hydrolysis solution is added and uniformly mixed, and then a gel is formed by aging at room temperature, and then the gel is transferred into a hydrothermal kettle for crystallization to obtain a Ce@ZSM-5 product. After centrifugation, washing, drying and grinding, the template agent is removed by calcination in an air atmosphere, and then ammonium ion exchange is performed to obtain a hydrogen type Ce@HZSM-5. The above carrier is mixed with a ruthenium chloride aqueous solution, and then loaded by using a wet impregnation method, dried, and reduced in a hydrogen-nitrogen mixed gas atmosphere to obtain a Ce@HZSM-5 zeolite molecular sieve wrapped with Ru. The product is used as a catalyst in a polyolefin (such as low-density polyethylene) hydrocracking reaction, and has the advantages of high conversion rate, high methane selectivity and good cycle stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This technology relates to the field of catalyst preparation technology, specifically to catalysts used in the hydrogenation and cracking reaction of polyolefins. Background Technology

[0002] Zeolites are crystalline aluminosilicates containing ordered molecular channels. Generally, the channels in zeolites can regulate molecular diffusion, leading to differential molecular transport and ultimately shape-selective catalysis. From their initial discovery as natural minerals to their subsequent large-scale commercial production, zeolites have played an indispensable role in various fields such as petroleum refining and chemical engineering. Among them, MFI-type ZSM-5 zeolite, with its unique three-dimensional cross-linked ten-membered ring channel structure, tunable acidity, and excellent hydrothermal stability, has become one of the most widely used molecular sieve materials in the field of catalytic cracking.

[0003] Ruthenium, rhodium, palladium, platinum, gold, and silver are considered the most effective catalysts for industrial catalysis, energy conversion, and environmental remediation. Considering practical applications and structural stability, porous zeolite materials, as supports for nano-metal dispersions, can enhance interactions and reduce the amount of precious metals used, thereby lowering catalyst costs. They have been used in the synthesis of supported precious metal catalysts. Their advantages lie in the strong interaction between the nano-metals and the zeolite support, which prevents metal particle aggregation. By constructing stable and uniformly dispersed metal clusters, high catalytic activity and low precious metal consumption are achieved, resulting in high contact and shape-selective catalytic capabilities. Among these, ruthenium-based catalysts have attracted widespread attention due to their excellent low-temperature C-C bond breaking activity and unique product selectivity in the hydrocracking reaction of polyolefins.

[0004] However, the distribution of acidic sites and the pore environment of a single zeolite support often fail to meet the requirements for efficient tandem catalysis. By introducing rare earth element Ce to modify zeolite, the number and intensity of acidic sites can be effectively controlled, and the pore confinement effect can be enhanced, thereby optimizing the synergistic catalytic performance of metal-acid bifunctional catalysts. This has significant application prospects in the hydrocracking and recycling of polyolefin waste.

[0005] The publication number is CN121449485A: Ru-supported mesoporous CeO2 catalyst is used for the hydrocracking of polyolefin plastics to produce methane. The disadvantages are that the precious metal ruthenium is expensive, the mechanical strength of the support is insufficient, the product is singular, and the reaction still requires medium-pressure hydrogen conditions.

[0006] The publication number is CN113797961A: a Ru-Ce bimetallic supported hierarchical porous ZSM-5 catalyst is used for the catalytic oxidation of chlorine-containing VOCs (such as chlorobenzene). The disadvantages are that the preparation process is complicated, the cost of precious metals is relatively high, and metal agglomeration is prone to occur at high temperatures, which leads to a decrease in activity.

[0007] Publication number CN103521257A: A conventional ZSM-5 molecular sieve catalyst modified with metal / heteropolyacid / superacid is applied to the dehydration of low-concentration ethanol to produce ethylene. The disadvantages are poor mass transfer efficiency, easy carbon deposition and deactivation, and the complexity of the system makes industrial scale-up and reproducibility difficult. Summary of the Invention

[0008] To address the shortcomings of existing technologies, the technical problem to be solved by this invention is to provide a catalyst for the hydrocracking reaction of polyolefins, wherein the catalyst is the ZSM-5 zeolite molecular sieve with in-situ Ce atom doped with Ru nanoparticles. The present invention also provides a method for preparing ZSM-5 zeolite molecular sieves loaded with Ru nanoparticles and in situ doped with Ce atoms.

[0009] To solve the above-mentioned technical problems, the technical solution adopted by the present invention is as follows: A catalyst for the hydrocracking reaction of polyolefins, wherein the zeolite molecular sieve has an MFI topology, and Ce is in trivalent form (Ce... 3+ The catalyst contains single-atom atomically dispersed Ru particles in the channels of ZSM-5 zeolite. Ru exists in the form of metallic (Ru0) nanoparticles with an average particle size of 2.0-3.0 nm and is highly dispersed on the zeolite support. The catalyst has Bronsted acid sites and Lewis acid sites. The introduction of Ce increases the number of strong acid sites and the total acid content compared to Ce-free HZSM-5. Ce atoms form Ce-O coordination with oxygen atoms in the zeolite framework, with a coordination number of 6.0-6.5 and a Ce-O bond length of 2.50-2.58 Å. The Ru-Ru coordination number of the Ru nanoparticles is 8.5-9.5, and the Ru-Ru bond length is 2.66-2.69 Å.

[0010] This catalyst is a bifunctional catalytic material constructed using ZSM-5 zeolite molecular sieve as a support. Cerium (Ce) atoms are introduced into the zeolite channels through an in-situ doping strategy, and ruthenium (Ru) nanoparticles are further loaded onto the sieve. Ce exists stably within the molecular sieve channels as highly dispersed trivalent single atoms, forming a characteristic coordination structure with framework oxygen atoms; Ru is highly dispersed on the support surface or within the channels as metallic nanoparticles. This structural design achieves a synergistic effect between acid and metal sites, making it suitable for the hydrocracking reaction of polyolefin plastics.

[0011] The preparation method of ZSM-5 zeolite molecular sieve loaded with Ru nanoparticles and doped with Ce atoms in situ is as follows: (1) Add the cerium source to a mixed solution of water and acid, and then add the silicon source; dissolve the aluminum source in the template agent; mix the two solutions to form a gel; (2) The aged gel was transferred to a hydrothermal reactor for crystallization to obtain in-situ Ce-doped ZSM-5 zeolite (Ce@ZSM-5). (3) Ce@ZSM-5 was ion-exchanged with an ammonium salt solution to obtain the hydrogen-form Ce@HZSM-5 support; (4) The ruthenium source was prepared into a solution and loaded onto the Ce@HZSM-5 support by impregnation method to obtain the Ru / Ce@ZSM-5 bifunctional catalyst.

[0012] The specific steps are as follows: (1) Add the cerium source to a mixed solution of water and acid, slowly add the silicon source, and stir at room temperature to hydrolyze; separately dissolve the aluminum source in the template agent, mix and age at room temperature to form a cerium-containing gel; (2) The aged gel was transferred to a hydrothermal reactor for crystallization. After centrifugation, washing, drying and grinding, in-situ Ce-doped ZSM-5 zeolite (Ce@ZSM-5) was obtained. (3) Ce@ZSM-5 was subjected to ion exchange with ammonium salt solution, and then dried and calcined to obtain hydrogen-form Ce@HZSM-5 support; (4) The ruthenium source was prepared into a solution and loaded onto the Ce@HZSM-5 support by impregnation. After drying, it was reduced in a hydrogen atmosphere to obtain the Ru / Ce@ZSM-5 bifunctional catalyst.

[0013] The steps of the polyolefin hydrogenation cracking reaction are as follows: (1) The hydrocracking reaction of LDPE was carried out in a 45 mL stainless steel high-temperature and high-pressure reactor. 100 mg of catalyst and 500 mg of LDPE were added to the bottom of the reactor in sequence to ensure uniform mixing of the catalyst and plastic. The reactor was then sealed. The air inside the reactor was replaced with hydrogen at least three times, and then hydrogen was introduced to the set pressure as the reaction gas. The reaction temperature and reaction time were set. After the reaction was completed, the reactor was placed in an ice-water bath to cool to below 20 °C, and the product was collected. (2) The gaseous products were collected in the airbag and analyzed using a gas chromatograph (FULI INSTRUMENTS, GC9790) equipped with an Al2O3 capillary column (30 m × 0.32 mm × 0.25 μm) and a flame ionization detector (FID); (3) Using dichloromethane as a solvent, n-octadecane (nC 28 Liquid products were treated as internal standards. Analysis was performed using a gas chromatograph (Agilent 7890) equipped with an RB-5 capillary column (50 m × 0.32 mm × 0.25 μm) and an FID detector. (4) Calculate the product yield and LDPE conversion using the following formulas: Yield (%) = (Product mass / Initial LDPE mass) × 100% LDPE conversion rate (%) = [1 - (remaining LDPE mass / initial LDPE mass)] × 100%.

[0014] The preferred catalysts are Ru / Ce@HZSM-5, Ru / 0.25%Ce@HZSM-5, Ru / 1%Ce@HZSM-5 or Ru / 2%Ce@HZSM-5.

[0015] Preferably, the cerium source in step (1) is one or more of cerium nitrate, cerium sulfate, and cerium chloride; the acid is one of hydrochloric acid, nitric acid, and sulfuric acid; the silicon source is one or more of tetraethyl orthosilicate, silica, and silica sol; the aluminum source is one of sodium aluminate, aluminum isopropoxide, and aluminum sulfate; and the template agent is one of tetrapropylammonium hydroxide and tetrapropylammonium bromide.

[0016] Preferably, the room temperature stirring aging time in step (1) is 12-24 hours.

[0017] Preferably, the molar ratio of the gel in step (1) is: silicon source: aluminum source: template agent: H2O: Ce = 1: 0.01-0.03: 0.2-0.5: 10-30: 0.002-0.01.

[0018] Preferably, the crystallization conditions in step (2) are: 150-180 °C for 5-7 days.

[0019] Preferably, the ammonium salt in step (3) is ammonium chloride; the ion exchange temperature is 70-90 °C and the exchange time is 6-8 hours; the calcination temperature is 500-600 °C and the time is 2-5 hours.

[0020] Preferably, the ruthenium source in step (4) is ruthenium trichloride; the reduction conditions are: 300-500 °C, reduction in a hydrogen-nitrogen mixed atmosphere for 2-4 hours.

[0021] The ZSM-5 zeolite molecular sieve product prepared by any of the above methods is a Ru nanoparticle-loaded, Ce-doped zeolite molecular sieve.

[0022] Preferably, the polyolefin is one or more of low-density polyethylene, high-density polyethylene, linear low-density polyethylene, and polypropylene.

[0023] Beneficial effects

[0024] The catalyst of this invention features Ru nanoparticles with a small average particle size (approximately 2.3 nm) and uniform dispersion, exhibiting strong metal-support interactions with Ce species and the zeolite framework, resulting in good structural stability. When this ZSM-5 zeolite molecular sieve, in situ doped with Ce atoms and supported on Ru nanoparticles, is used as a catalyst in the hydrocracking reaction of polyolefins, it demonstrates high catalytic conversion (close to 100%), excellent methane selectivity (up to 99%), a TON of 6317, and a TOF of 3158 h⁻¹. -1 The space-time yield of methane reached 495 g CH4·gcat. -1 h -1 Simultaneously, by mildly controlling the reaction conditions, the product can be directionally switched from methane to ethane, with an ethane yield of up to 37%, demonstrating flexible product adjustability. Furthermore, this catalyst exhibits good cycle stability and high precious metal utilization, showing promising industrial application prospects in the chemical upgrading and recycling of waste polyolefin plastics.

[0025] This invention provides a method for preparing ZSM-5 zeolite molecular sieves loaded with Ru nanoparticles and in situ doped with Ce atoms. The Ce species are encapsulated in the ZSM-5 channels in an atomically dispersed form by a one-step hydrothermal method of acid hydrolysis, and then Ru nanoparticles are loaded onto the support in a highly dispersed manner by impregnation reduction. Attached Figure Description

[0026] Figure 1 XRD patterns of Ru / Ce@HZSM-5 and control samples Ru / HZSM-5, Ce@HZSM-5, and HZSM-5; Figure 2 SEM images of Ru / Ce@HZSM-5 and control samples Ru / HZSM-5, Ce@HZSM-5, and HZSM-5; Figure 3 TEM image of Ru / Ce@HZSM-5; Figure 4 Nitrogen adsorption-desorption curves and pore size distribution diagrams for Ru / Ce@HZSM-5 and control samples Ru / HZSM-5, Ce@HZSM-5, and HZSM-5; Figure 5 R-space fitting curves for Ru K-edge EXAFS of Ru / Ce@HZSM-5 and Ru / HZSM-5; Figure 6 R-space fitting curves of Ce L-edge EXAFS for Ru / Ce@HZSM-5 and Ce@HZSM-5; Figure 7 Infrared spectra of NH3-TPD and pyridine for Ce@HZSM-5 and HZSM-5; Figure 8 The refined Rietveld structure spectrum of Ce@HZSM-5 by synchrotron radiation powder X-ray diffraction (PXRD); Figure 9 The graph shows the hydrocracking performance of low-density polyethylene (LDPE) for Ru / Ce@HZSM-5 and control samples Ru / HZSM-5, Ce@HZSM-5, and HZSM-5.

[0027] Figure 10 The graph shows the performance of Ru / Ce@HZSM-5 in regulating ethane products in low-density polyethylene at low temperatures.

[0028] Figure 11 Breakthrough kinetic curves for Ce@HZSM-5 and HZSM-5 at 298 K for a CH4 / C2H6 gas mixture (60 / 40 v / v).

[0029] Figure 12 The graph shows the properties of Ru / Ce@HZSM-5 in different plastic hydrocracking products.

[0030] Figure 13 Figure 1 shows the hydrocracking performance of low-density polyethylene with different Ce-doped catalysts. Detailed Implementation

[0031] To facilitate understanding of the technical solution of this application, some concepts involved in this application will be explained below.

[0032] Example 1

[0033] 0.0229 g of cerium nitrate hexahydrate (Ce(NO3)3·6H2O) was dissolved in a mixed solution of 4 g deionized water and 0.43 g hydrochloric acid (HCl), and 5 g of tetraethyl orthosilicate (TEOS) was slowly added. The mixture was stirred at room temperature for 24 h to allow complete hydrolysis of the silicon source. Separately, 0.05 g of sodium aluminate (NaAlO2) was dissolved in a solution of 7.8 g tetrapropylammonium hydroxide (TPAOH, 25 wt%) to form a clear solution. The two solutions were mixed and aged at room temperature for another 24 h with stirring to form a homogeneous gel.

[0034] The final molar ratio of the gel was: SiO2: Al2O3: TPAOH: H2O: Ce = 1: 0.018: 0.35: 22: 0.0025. After aging, the gel was transferred to a stainless steel hydrothermal reactor with a polytetrafluoroethylene liner and statically hydrothermally crystallized at 170 °C for 4 days. After crystallization, the solid was separated by centrifugation, washed with deionized water until neutral, dried at 100 °C overnight, ground into powder, and then calcined in air at 550 °C for 300 min to remove the template agent, yielding Ce@ZSM-5 zeolite raw powder.

[0035] The above raw powder was mixed with 1 mol / L NH4Cl solution at a mass-volume ratio of 1:20, and ion exchange was carried out by stirring in an 80 °C water bath for 2 h. After the exchange was completed, the mixture was centrifuged, dried at 100 °C, and then calcined in a muffle furnace at 550 °C for 120 min to obtain the hydrogen-form Ce@HZSM-5 support.

[0036] Take 0.3 g of Ce@HZSM-5 support, add 0.1 mol / L RuCl3·xH2O solution (the required volume is calculated based on the theoretical Ru loading of 0.5 wt%), stir and impregnate at room temperature, dry in a water bath at 80 °C overnight, and then reduce at 500 °C in H2 atmosphere to finally obtain the target catalyst, denoted as Ru / Ce@HZSM-5.

[0037] Example 2

[0038] 0.0145 g of cerium nitrate hexahydrate (Ce(NO3)3·6H2O) was dissolved in a mixed solution of 4 g of deionized water and 0.43 g of hydrochloric acid (HCl), and 5 g of tetraethyl orthosilicate (TEOS) was slowly added. The mixture was stirred at room temperature for 24 h to allow complete hydrolysis of the silicon source. Separately, 0.05 g of sodium aluminate (NaAlO2) was dissolved in a solution of 7.8 g of tetrapropylammonium hydroxide (TPAOH, 25 wt%) to form a clear solution. The two solutions were mixed and aged at room temperature for another 24 h with stirring to form a homogeneous gel.

[0039] The final molar ratio of the gel was: SiO2: Al2O3: TPAOH: H2O: Ce = 1: 0.018: 0.35: 22: 0.00125. After aging, the gel was transferred to a stainless steel hydrothermal reactor with a polytetrafluoroethylene liner and statically hydrothermally crystallized at 170 °C for 4 days. After crystallization, the solid was separated by centrifugation, washed with deionized water until neutral, dried at 100 °C overnight, ground into powder, and then calcined in air at 550 °C for 300 min to remove the template agent, yielding 0.25% Ce@ZSM-5 zeolite powder.

[0040] The above raw powder was mixed with 1 mol / L NH4Cl solution at a mass-to-volume ratio of 1:20, and ion exchange was carried out by stirring in an 80 °C water bath for 2 h. After the exchange was completed, the mixture was centrifuged, dried at 100 °C, and then calcined in a muffle furnace at 550 °C for 120 min to obtain the hydrogen form 0.25%Ce@HZSM-5 support.

[0041] Take 0.3 g of 0.25%Ce@HZSM-5 support, add 0.1 mol / L RuCl3·xH2O solution (the required volume is calculated based on the theoretical Ru loading of 0.5 wt%), stir and impregnate at room temperature, dry in a water bath at 80 °C overnight, and then reduce at 500 °C in H2 atmosphere to finally obtain the target catalyst, denoted as Ru / 0.25%Ce@HZSM-5.

[0042] Example 3

[0043] 0.0458 g of cerium nitrate hexahydrate (Ce(NO3)3·6H2O) was dissolved in a mixed solution of 4 g deionized water and 0.43 g hydrochloric acid (HCl), and 5 g of tetraethyl orthosilicate (TEOS) was slowly added. The mixture was stirred at room temperature for 24 h to allow complete hydrolysis of the silicon source. Separately, 0.05 g of sodium aluminate (NaAlO2) was dissolved in a solution of 7.8 g tetrapropylammonium hydroxide (TPAOH, 25 wt%) to form a clear solution. The two solutions were mixed and aged at room temperature for another 24 h with stirring to form a homogeneous gel.

[0044] The final molar ratio of the gel was: SiO2: Al2O3: TPAOH: H2O: Ce = 1: 0.018: 0.35: 22: 0.005. After aging, the gel was transferred to a stainless steel hydrothermal reactor with a polytetrafluoroethylene liner and statically hydrothermally crystallized at 170 °C for 4 days. After crystallization, the solid was separated by centrifugation, washed with deionized water until neutral, dried at 100 °C overnight, ground into powder, and then calcined in air at 550 °C for 300 min to remove the template agent, yielding 1% Ce@ZSM-5 zeolite powder.

[0045] The above raw powder was mixed with 1 mol / L NH4Cl solution at a mass-volume ratio of 1:20, and ion exchange was carried out by stirring in an 80 °C water bath for 2 h. After the exchange was completed, the mixture was centrifuged, dried at 100 °C, and then calcined in a muffle furnace at 550 °C for 120 min to obtain the hydrogen form 1%Ce@HZSM-5 support.

[0046] Take 0.3 g of 1%Ce@HZSM-5 support, add 0.1 mol / L RuCl3·xH2O solution (the required volume is calculated based on the theoretical Ru loading of 0.5 wt%), stir and impregnate at room temperature, dry in a water bath at 80 °C overnight, and then reduce at 500 °C in H2 atmosphere to finally obtain the target catalyst, denoted as Ru / 1%Ce@HZSM-5.

[0047] Example 4

[0048] 0.0916 g of cerium nitrate hexahydrate (Ce(NO3)3·6H2O) was dissolved in a mixed solution of 4 g deionized water and 0.43 g hydrochloric acid (HCl), and 5 g of tetraethyl orthosilicate (TEOS) was slowly added. The mixture was stirred at room temperature for 24 h to allow complete hydrolysis of the silicon source. Separately, 0.05 g of sodium aluminate (NaAlO2) was dissolved in a solution of 7.8 g tetrapropylammonium hydroxide (TPAOH, 25 wt%) to form a clear solution. The two solutions were mixed and aged at room temperature for another 24 h with stirring to form a homogeneous gel.

[0049] The final molar ratio of the gel was: SiO2: Al2O3: TPAOH: H2O: Ce = 1: 0.018: 0.35: 22: 0.01. After aging, the gel was transferred to a stainless steel hydrothermal reactor with a polytetrafluoroethylene liner and statically hydrothermally crystallized at 170 °C for 4 days. After crystallization, the solid was separated by centrifugation, washed with deionized water until neutral, dried at 100 °C overnight, ground into powder, and then calcined in air at 550 °C for 300 min to remove the template agent, yielding 2% Ce@ZSM-5 zeolite powder.

[0050] The above raw powder was mixed with 1 mol / L NH4Cl solution at a mass-volume ratio of 1:20, and ion exchange was carried out by stirring in an 80 °C water bath for 2 h. After the exchange was completed, the mixture was centrifuged, dried at 100 °C, and then calcined in a muffle furnace at 550 °C for 120 min to obtain the hydrogen form 2%Ce@HZSM-5 support.

[0051] Take 0.3 g of 2%Ce@HZSM-5 support, add 0.1 mol / L RuCl3·xH2O solution (the required volume is calculated based on the theoretical Ru loading of 0.5 wt%), stir and impregnate at room temperature, dry in a water bath at 80 °C overnight, and then reduce at 500 °C in H2 atmosphere to finally obtain the target catalyst, denoted as Ru / 2%Ce@HZSM-5.

[0052] Comparative Example 1

[0053] 0.0229 g of cerium nitrate hexahydrate (Ce(NO3)3·6H2O) was dissolved in a mixed solution of 4 g of deionized water and 0.43 g of hydrochloric acid (HCl), and 5 g of tetraethyl orthosilicate (TEOS) was slowly added. The mixture was stirred at room temperature for 24 h to allow the silicon source to be fully hydrolyzed.

[0054] Separately, 0.05 g of sodium aluminate (NaAlO2) was dissolved in 7.8 g of tetrapropylammonium hydroxide (TPAOH, 25 wt%) solution to form a clear solution. The two solutions were mixed and aged at room temperature for 24 h with stirring to form a homogeneous gel. The final molar ratio of the gel was: SiO2: Al2O3: TPAOH: H2O: Ce = 1: 0.018: 0.35: 22: 0.0025. After aging, the gel was transferred to a stainless steel hydrothermal reactor with a polytetrafluoroethylene liner and statically hydrothermally crystallized at 170 °C for 4 days. After crystallization, the solid was separated by centrifugation, washed with deionized water until neutral, dried overnight at 100 °C, ground into powder, and calcined in air at 550 °C for 300 min to remove the template agent, yielding Ce@ZSM-5 zeolite raw powder. The above raw powder was mixed with 1 mol / L NH4Cl solution at a mass-to-volume ratio of 1:20, and ion exchange was carried out by stirring in an 80 °C water bath for 2 h. After the exchange was completed, the mixture was centrifuged, dried at 100 °C, and then calcined in a muffle furnace at 550 °C for 120 min to obtain the hydrogen-form Ce@HZSM-5 support, denoted as Ce@HZSM-5.

[0055] Comparative Example 2

[0056] Mix 4 g of deionized water and 0.43 g of hydrochloric acid (HCl), slowly add 5 g of tetraethyl orthosilicate (TEOS), and stir at room temperature for 24 h to allow the silicon source to be fully hydrolyzed.

[0057] Separately, 0.05 g of sodium aluminate (NaAlO2) was dissolved in 7.8 g of tetrapropylammonium hydroxide (TPAOH, 25 wt%) solution to form a clear solution. The two solutions were mixed and aged at room temperature for 24 h with stirring to form a homogeneous gel. The final molar ratio of the gel was: SiO2: Al2O3: TPAOH: H2O = 1: 0.018: 0.35: 22. After aging, the gel was transferred to a stainless steel hydrothermal reactor with a polytetrafluoroethylene liner and statically hydrothermally crystallized at 170 °C for 4 days. After crystallization, the solid was separated by centrifugation, washed with deionized water until neutral, dried overnight at 100 °C, ground into powder, and calcined in air at 550 °C for 300 min to remove the template agent, yielding ZSM-5 zeolite raw powder. The above raw powder was mixed with 1 mol / L NH4Cl solution at a mass-volume ratio of 1:20, and ion exchange was carried out by stirring in an 80 °C water bath for 2 h. After the exchange was completed, the mixture was centrifuged, dried at 100 °C, and then calcined in a muffle furnace at 550 °C for 120 min to obtain the hydrogen form HZSM-5 support, denoted as HZSM-5.

[0058] Comparative Example 3

[0059] Mix 4 g of deionized water and 0.43 g of hydrochloric acid (HCl), slowly add 5 g of tetraethyl orthosilicate (TEOS), and stir at room temperature for 24 h to allow the silicon source to be fully hydrolyzed.

[0060] Separately, 0.05 g of sodium aluminate (NaAlO2) was dissolved in 7.8 g of tetrapropylammonium hydroxide (TPAOH, 25 wt%) solution to form a clear solution. The two solutions were mixed and aged at room temperature for 24 h with stirring to form a homogeneous gel. The final molar ratio of the gel was: SiO2: Al2O3: TPAOH: H2O = 1: 0.018: 0.35: 22. After aging, the gel was transferred to a stainless steel hydrothermal reactor with a polytetrafluoroethylene liner and statically hydrothermally crystallized at 170 °C for 4 days. After crystallization, the solid was separated by centrifugation, washed with deionized water until neutral, dried overnight at 100 °C, ground into powder, and calcined in air at 550 °C for 300 min to remove the template agent, yielding ZSM-5 zeolite raw powder. The above-mentioned raw powder was mixed with 1 mol / L NH4Cl solution at a mass-to-volume ratio of 1:20, and ion exchange was carried out by stirring in an 80 °C water bath for 2 h. After the exchange was completed, the mixture was centrifuged, dried at 100 °C, and then calcined in a muffle furnace at 550 °C for 120 min to obtain the hydrogen form HZSM-5 support. 0.3 g of the HZSM-5 support was taken and added to 0.1 mol / L RuCl3·xH2O solution (the required volume was calculated based on the theoretical Ru loading of 0.5 wt%). The mixture was stirred and impregnated at room temperature, dried overnight in an 80 °C water bath, and then reduced at 500 °C in an H2 atmosphere to obtain the control catalyst, denoted as Ru / HZSM-5. XRF analysis showed that the actual Ru loading in the obtained catalyst was 0.42 wt%.

[0061] Example 5

[0062] The samples prepared in Example 1 and Comparative Examples 1-3 were subjected to structural characterization and related performance tests, and the results are as follows: Figure 1-7 As shown: Figure 1 The images show the XRD patterns of the sample from Example 1 and the comparative sample. The peaks exhibited by these samples are typical structural diffraction peaks of MFI-type zeolites, indicating that the samples have good crystallinity. The loading of Ru nanoparticles and the in-situ doping of Ce atoms did not reduce the crystallinity of the samples.

[0063] Figure 2 These are SEM images of the sample from Example 1 and the comparative sample. It can be seen that the synthesized sample is elliptical cylindrical and has a similar morphology.

[0064] Figure 3 This is a TEM image of the sample from Example 1, showing the particle size distribution statistics. Figure 3 B) shows that the particle diameter is mainly concentrated between 2-4 nm, with an average particle size of about 2.3 nm, indicating that Ru has excellent dispersibility on this support and no obvious agglomeration occurs.

[0065] Figure 4 These are the nitrogen adsorption-desorption curves and pore size distributions of the sample from Example 1 and the comparative sample. All samples in the series exhibit typical adsorption-desorption curves for microporous materials, with specific surface areas ranging from 370 to 450 m². 2 g -1 The pore volume is in the range of 0.22-0.24 cm³. 3 g -1 These results indicate that the introduction of Ce and the loading of Ru did not cause blockage or damage to the pore structure of the molecular sieve.

[0066] Figure 5 EXAFS plots of Ru in Ru / Ce@HZSM-5 and Ru / HZSM-5 are shown, illustrating the coordination states of Ru in the two samples. This indicates that Ru in Ru / Ce@HZSM-5 is primarily in the metallic state. 0 It exists in form.

[0067] Figure 6 EXAFS plots of Ce in Ru / Ce@HZSM-5 and Ru / HZSM-5 are shown, illustrating the coordination states of Ce in the two samples. This indicates that Ce mainly exists as Ce. 3+ The state exists.

[0068] Figure 7 Zeolite acidity characterization results showed that the acid strength and acid content of Ce@HZSM-5 were significantly higher than those of unmodified HZSM-5, indicating that the introduction of Ce effectively controlled acidity. Figure 7 A). Pyridine adsorption infrared spectroscopy ( Figure 7 The results of B) clearly show that the introduction of Ce not only increased the acidity, but also significantly altered the type and intensity distribution of acid sites.

[0069] Figure 8 The image shows the refined Rietveld structure obtained by synchrotron radiation powder X-ray diffraction (PXRD) of Comparative Example 1 (Ce@HZSM-5). The refinement results show that Ce@HZSM-5 maintains a complete MFI topology without impurities or framework disruption. Ce atoms are preferentially located within the sinusoidal channels of the MFI framework, with an occupancy of 0.04375 and a minimum distance of 2.541 Å to framework oxygen atoms. Combined with XAFS analysis, Ce exists in an atomically dispersed form within the zeolite channels in a highly distorted multi-oxygen coordination environment, with an average Ce−O coordination number of approximately 6 and an average bond length similar to the refined value. These results demonstrate that Ce sites are stably confined within the channels and provide a structural basis for the regulation of the zeolite acid site topology.

[0070] Example 6

[0071] The samples prepared in Example 1 and Comparative Examples 1-3 were subjected to low-density polyethylene (LDPE) hydrocracking reaction, and the specific operation was as follows: The reaction was carried out in a 45 ml stainless steel high-temperature and high-pressure reactor for the hydrocracking of LDPE. Catalyst (100 mg) and LDPE (500 mg) were added sequentially to the bottom of the reactor containing a high-temperature rotor to ensure uniform mixing. The reactor was then sealed, and hydrogen was purged at least three times to ensure the removal of air from the reactor and to bring it to the required pressure as the reaction gas. The reaction temperature and time were set. After the reaction, the reactor was placed in an ice-water bath until the temperature dropped below 20 °C for product collection. The gaseous products were collected in a safety gasket. Detection was performed using a gas chromatograph (FULIINSTRUMENTS, GC9790) equipped with an Al₂O₃ capillary column (30 m × 0.32 mm × 0.25 μm) and a flame ionization detector (FID). Liquid phase products were analyzed using dichloromethane as solvent and n-octacosan as an internal standard. Liquid chromatography was performed using gas chromatography (GC, Agilent 7890), filtered through an RB-5 capillary column (50 m × 0.32 mm × 0.25 μm), with a flame ionization detector (FID). nC 28 This is an internal standard.

[0072] The formulas for calculating yield and conversion rate are as follows: Yield (%) = [Product mass / Initial LDPE mass] × 100% LDPE conversion rate (%) = [1 − (remaining LDPE mass / initial LDPE mass) × 100%.

[0073] TON: The total number of catalytic cycles that a single active site of the catalyst can complete in a reaction, reflecting the overall catalytic efficiency and stability of the catalyst. TOF: The number of catalytic cycles completed by a single active site of a catalyst per unit time, reflecting the intrinsic catalytic activity of the catalyst.

[0074] Table 1 shows the hydrocracking conversion activity, reaction rate, and TOF of low-density polyethylene in Example 1 and Comparative Examples 1-3. Example 1 has the best activity.

[0075] Table 1: Comparison of the reaction performance of catalysts

[0076] Reaction conditions: 270 °C, 3 MPa H2, 2 h, 0.1 g Ru / Ce@HZSM-5, 0.5 g LDPE. LDPE conversion rate (%) = [1 − (remaining LDPE mass / initial LDPE mass) × 100%] Yield (%) = [Product mass / Initial LDPE mass] × 100%. Figure 9 The effects of four catalysts—Ce@ZSM-5, HZSM-5, Ru / Ce@HZSM-5, and Ru / HZSM-5—on the hydrocracking performance of LDPE were systematically compared under the following reaction conditions (270 °C, 3 MPa H2, reaction time 2 h, catalyst to LDPE mass ratio 1:5). The results are as follows: Figure 6 As shown in Table 1, Ru / Ce@HZSM-5 exhibited the highest catalytic activity in terms of conversion rate, achieving LDPE conversion of 99%, significantly higher than Ce@ZSM-5 (60%), HZSM-5 (55%), and Ru / HZSM-5 (45%). This indicates that the coexistence of Ru and Ce plays a crucial role in enhancing the overall reactivity of the catalyst. Regarding product distribution, Ru / Ce@HZSM-5 almost completely converted LDPE to gaseous alkanes (C1-C4), with a CH4 selectivity as high as 99%, C2H6 accounting for only 0.37%, and no C3-C4 products. This demonstrates that this catalyst has a significant advantage in promoting continuous C / C bond breaking and directional CH4 formation.

[0077] Example 7 The sample prepared in Example 1 was used to catalyze the adjustment of ethane product conditions in low-density polyethylene under low-temperature conditions: The reaction was carried out in a 45 ml stainless steel high-temperature and high-pressure reactor for the hydrocracking of LDPE. Catalyst (100 mg) and LDPE (500 mg) were added sequentially to the bottom of the reactor containing a high-temperature rotor to ensure uniform mixing. The reactor was then sealed, and hydrogen was purged at least three times to ensure the removal of air from the reactor and to bring it to the required pressure as the reaction gas. The reaction temperature and time were set. After the reaction, the reactor was placed in an ice-water bath until the temperature dropped below 20 °C for product collection. The gaseous products were collected in a safety gasket. Detection was performed using a gas chromatograph (FULIINSTRUMENTS, GC9790) equipped with an Al₂O₃ capillary column (30 m × 0.32 mm × 0.25 μm) and a flame ionization detector (FID). Liquid phase products were analyzed using dichloromethane as solvent and n-octacosan as an internal standard. Liquid chromatography was performed using gas chromatography (GC, Agilent 7890), filtered through an RB-5 capillary column (50 m × 0.32 mm × 0.25 μm), with a flame ionization detector (FID). nC 28 This is an internal standard.

[0078] The formulas for calculating yield and conversion rate are as follows: Yield (%) = [Product mass / Initial LDPE mass] × 100% LDPE conversion rate (%) = [1 - (remaining LDPE mass / initial LDPE mass) × 100%.

[0079] The sample obtained in Example 1 was used to catalyze the adjustment of ethane production in low-density polyethylene under low-temperature conditions. The conversion and yield were calculated and are shown in Table 2 below. Table 2: Optimization of reaction conditions for Ru / Ce@HZSM-5.

[0080]

[0081] Reaction conditions: Catalyst Ru / Ce@HZSM-5, 0.5 g plastic. LDPE conversion rate (%) = [1 - (remaining LDPE mass / initial LDPE mass) × 100%] Yield (%) = [Product mass / Initial LDPE mass] × 100%. In addition to precise control of CH4 selectivity, product distribution can be intentionally directed towards a CH4 / C2H6-rich mixture by optimizing reaction conditions. Notably, under mild conditions of 230 °C and 3 MPa H2, the yield of C2H6 can reach up to 37%. Figure 10 (See Table 2). However, when the reaction temperature was further reduced to 220-210 °C, the reaction kinetics slowed down significantly, leading to incomplete LDPE conversion and a wider product distribution, generating a series of C1-C4 hydrocarbons. This phenomenon indicates that there is a critical kinetic window in this hydrocracking process; excessively high temperatures easily lead to deep cracking to CH4, while excessively low temperatures result in insufficient activation energy to achieve selective bond breaking.

[0082] Example 8

[0083] A dynamic breakthrough experiment was conducted on the sample of the control group 1, as follows: To address the separation problem of the product mixture, this study further investigated the separation performance of the adsorbent. To simulate actual operating conditions, a dynamic breakthrough experiment was conducted using a C2H6 / CH4 (40 / 60, v / v) gas mixture. Figure 11 Dynamic breakthrough experiments were conducted on a gas separation apparatus (HP-MC41). Adsorbent (1.9 g) was packed into a stainless steel column (inner diameter: 6 mm; bed length: 14 cm) and pretreated at 300 °C for 5 h under dynamic vacuum. Before each measurement, a flow rate of 5 mL / min was used. -1 The column was purged with helium (He). The flow rate was increased by 2.0 mL / min. -1A CH4 / C2H6 mixture (60 / 40, volume ratio) was introduced at a total flow rate for breakthrough testing. For cyclic breakthrough experiments, the adsorbent was regenerated using the same pretreatment procedure before each cycle. Results showed that Ce@HZSM-5 exhibited a slightly longer retention time for C2H6 compared to HZSM-5, further confirming its high efficiency in separating ethane / methane mixtures (separation ratio of 23.4). In summary, the Ru / Ce@HZSM-5 catalytic system can achieve on-demand control of polyethylene hydrocracking products by adjusting reaction parameters, and its modified zeolite framework also endows it with excellent downstream separation performance.

[0084] Example 9

[0085] The samples prepared in Example 1 were used in different hydrocracking reactions of plastics, as detailed below: In addition to low-density polyethylene (LDPE), we systematically evaluated the hydrogenolysis performance of the Ru / Ce@HZSM-5 catalyst on other polyolefin substrates, including linear low-density polyethylene (LLDPE), polypropylene (PP), and high-density polyethylene (HDPE). The reaction was carried out in a 45 ml stainless steel high-temperature and high-pressure reactor for polyolefin hydrocracking. The catalyst (100 mg) and polyolefin (500 mg) were added sequentially to the bottom of the reactor containing a high-temperature rotor to ensure homogeneous mixing. The reactor was sealed, and hydrogen was then purged at least three times to ensure the removal of air from the reactor and to bring the hydrogen to the required pressure as the reaction gas. The reaction temperature and time were set. After the reaction, the reactor was placed in an ice-water bath until the temperature dropped below 20 °C for product collection. The gaseous products were collected in a safety gasbag. Detection was performed on a gas chromatograph (FULIINSTRUMENTS, GC9790) equipped with an Al₂O₃ capillary column (30 m × 0.32 mm × 0.25 μm) and a flame ionization detector (FID). Liquid products were analyzed using dichloromethane as solvent and n-octadecane as internal standard. Liquid chromatography was performed using gas chromatography (GC, Agilent 7890), filtered through an RB-5 capillary column (50 m × 0.32 mm × 0.25 μm), with a flame ionization detector (FID) and nC. 28 This is an internal standard.

[0086] The formulas for calculating yield and conversion rate are as follows: Yield (%) = [Product mass / Initial LDPE mass] × 100% LDPE conversion rate (%) = [1 - (remaining LDPE mass / initial LDPE mass) × 100%.

[0087] like Figure 12As shown in the reaction conditions (270 °C, 3 MPa H2, 2 h, 0.1 g Ru / Ce@HZSM-5, 0.5 g plastic), all these polyolefin feedstocks were effectively converted into methane. The methane selectivity of LDPE, LLDPE, PP and HDPE all exceeded 97%, and the conversion rate all reached over 98%. This fully demonstrates that the catalyst maintains excellent and stable C-C bond breaking ability and CH4 directional generation performance when facing polyolefins with different polymerization structures and chain structures.

[0088] Example 10

[0089] The samples prepared in Examples 1-4 were used in the hydrocracking reaction of low-density polyethylene, as detailed below: The effect of Ce doping concentration on catalyst performance was further investigated (reaction conditions: 30 bar H2, 270 °C, 2 h, 0.1 g catalyst, 0.5 g LDPE). The reaction was carried out in a 45 ml stainless steel high-temperature and high-pressure reactor for LDPE hydrocracking. The catalyst (100 mg) and LDPE (500 mg) were added sequentially to the bottom of the reactor containing a high-temperature rotor to ensure uniform mixing. The reactor was sealed, and hydrogen was then purged at least three times to ensure the removal of air from the reactor and to bring the hydrogen to the required pressure as the reaction gas. The reaction temperature and time were set. After the reaction, the reactor was placed in an ice-water bath until the temperature dropped below 20 °C for product collection. The gaseous products were collected in a safety gasket. Detection was performed on a gas chromatograph (FULI INSTRUMENTS, GC9790) equipped with an Al2O3 capillary column (30 m × 0.32 mm × 0.25 μm) and a flame ionization detector (FID). Liquid products were analyzed using dichloromethane as solvent and n-octadecane as internal standard. Liquid chromatography was performed using gas chromatography (GC, Agilent 7890), filtered through an RB-5 capillary column (50 m × 0.32 mm × 0.25 μm), with a flame ionization detector (FID) and nC. 28 This is an internal standard.

[0090] The formulas for calculating yield and conversion rate are as follows: Yield (%) = [Product mass / Initial LDPE mass] × 100% LDPE conversion rate (%) = [1 − (remaining LDPE mass / initial LDPE mass) × 100%.

[0091] When the Ce doping concentration is 0.5 wt%, the Ru / Ce@HZSM-5 catalyst exhibits the best activity and selectivity: LDPE conversion reaches 100%, and methane selectivity is 99%. Figure 13When the Ce doping concentration increased to 2 wt% (Ru / 2%Ce@HZSM-5), the LDPE conversion decreased to 80%, and the methane selectivity decreased to 41%. Analysis showed that excess Ce may form nanoparticles or clusters, blocking the pores of ZSM-5 zeolite, or covering some acidic sites and metal active centers, resulting in a significant site-blocking effect and thus deteriorating catalytic performance. Therefore, the preferred Ce doping concentration is 0.5 wt%.

Claims

1. A catalyst for the hydrocracking reaction of polyolefins, characterized in that, The catalyst uses ZSM-5 zeolite molecular sieve as a carrier, and introduces cerium atoms into the zeolite channels through in-situ doping. The cerium atoms are atomically dispersed in the channels of ZSM-5 zeolite molecular sieve in the form of trivalent single atoms, forming a Ce-O coordination structure with oxygen atoms in ZSM-5 zeolite molecular sieve, and further loading ruthenium nanoparticles.

2. The catalyst according to claim 1, characterized in that, The Ce-O coordination number is 6.0-6.5 and the Ce-O bond length is 2.50-2.58 Å; the Ru-Ru coordination number of the Ru nanoparticles is 8.5-9.5 and the Ru-Ru bond length is 2.66-2.69 Å.

3. The catalyst according to claim 1, characterized in that, The polyolefin is one or more of low-density polyethylene, high-density polyethylene, linear low-density polyethylene, and polypropylene.

4. The catalyst according to claim 1, characterized in that, The catalyst encapsulates Ce species in atomically dispersed form within the channels of ZSM-5 zeolite molecular sieve via a one-step hydrothermal acid hydrolysis method, and then loads Ru nanoparticles onto the ZSM-5 zeolite molecular sieve support in a highly dispersed manner through impregnation reduction.

5. The catalyst according to claim 1, characterized in that, The catalyst is prepared as follows: (1) Add the cerium source to a mixed solution of water and acid, and then add the silicon source; dissolve the aluminum source in the template agent; mix the two solutions to form a gel; (2) The aged gel was transferred to a hydrothermal reactor for crystallization to obtain Ce@ZSM-5 zeolite with in-situ Ce doping; (3) Ce@ZSM-5 was ion-exchanged with an ammonium salt solution to obtain the hydrogen-form Ce@HZSM-5 support; (4) The ruthenium source was prepared into a solution and loaded onto the Ce@HZSM-5 support by impregnation method to obtain the Ru / Ce@ZSM-5 bifunctional catalyst.

6. The catalyst according to claim 5, characterized in that: The catalyst is Ru / Ce@HZSM-5, Ru / 0.25%Ce@HZSM-5, Ru / 1%Ce@HZSM-5 or Ru / 2%Ce@HZSM-5.

7. The catalyst according to claim 5, characterized in that, The cerium source in step (1) is one or more of cerium nitrate, cerium sulfate, and cerium chloride; the acid is one of hydrochloric acid, nitric acid, and sulfuric acid; the silicon source is one or more of tetraethyl orthosilicate, silica, and silica sol; the aluminum source is one of sodium aluminate, aluminum isopropoxide, and aluminum sulfate; and the template agent is one of tetrapropylammonium hydroxide and tetrapropylammonium bromide.

8. The catalyst according to claim 5, characterized in that, In step (1), the two solutions are mixed and aged at room temperature with stirring for 12-24 hours.

9. The catalyst according to claim 5, characterized in that, The molar ratio of the gel in step (1) is: silicon source: aluminum source: template agent: H2O: Ce = 1 : 0.01-0.03 : 0.2-0.5 : 10-30 : 0.002-0.01; The crystallization conditions described in step (2) are: 150-180 °C, 5-7 days; The ammonium salt solution in step (3) is ammonium chloride, and is prepared as a 1 mol / L ammonium chloride aqueous solution. Ion exchange is carried out at a catalyst to ammonium chloride aqueous solution mass ratio of 1:

20. The ion exchange temperature is 70-90 °C and the exchange time is 6-8 hours. After crystallization, calcination is carried out at a temperature of 500-600 °C for 2-5 hours. The ruthenium source in step (4) is ruthenium trichloride, which is prepared as a 0.1 mol / L ruthenium chloride aqueous solution and impregnated and loaded according to the required Ru; after loading, a reduction reaction is carried out, and the reduction conditions are: 300-500 °C, reduction in a hydrogen-nitrogen mixed atmosphere for 2-4 hours.

10. The catalyst according to any one of claims 1-9, characterized in that, The catalyst, after being mixed with polyolefin, is subjected to a hydrocracking reaction in a hydrogen atmosphere at 230–280 °C and 1–4 MPa.

Citation Information

Patent Citations

  • ZSM-5 molecular sieve modified catalyst as well as preparation method and application thereof

    CN103521257A

  • RuCe / ZSM-5 molecular sieve catalyst as well as preparation method and application thereof

    CN113797961A

  • Method for preparing methane by catalyzing polyolefin plastic hydrocracking through ruthenium-based cerium dioxide

    CN121449485A